2010
DOI: 10.1680/macr.2010.62.3.163
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the transport properties of a blended concrete from its electrical properties measured during a migration test

Abstract: The Nernst-Planck equation describes ionic movements in saturated porous materials subject to chemical concentration gradients in the pore fluid and applied electric fields. When applied to a macroscopic system the equation supposes that the flux of each ion is independent of every other one. However, owing to the ionic exchange among different or similar species, there are ionic potentials that affect the final flux. These will distort the applied electric field and thus keep the electroneutrality of the sum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Additionally, the voltage membrane potential was calculated using a salt bridge in a drilled hole in the top of the sample giving readings of the actual voltage in the sample during the test (Figure 3). These readings confirmed that the voltage drop across the sample is not linear and varies with time 10,11 .…”
Section: Test Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…Additionally, the voltage membrane potential was calculated using a salt bridge in a drilled hole in the top of the sample giving readings of the actual voltage in the sample during the test (Figure 3). These readings confirmed that the voltage drop across the sample is not linear and varies with time 10,11 .…”
Section: Test Methodssupporting
confidence: 53%
“…The chloride related transport properties needed to simulate the chloride effects on a voltage or current control test for the mixture proposed were obtained from the experimental voltage control results by feeding an artificial neural network with results from the electrochemical model 10,11 . Table 2 is a summary of the principal transport properties and variables obtained following that methodology.…”
Section: Calculation Of Transport Propertiesmentioning
confidence: 99%
“…There are two methods to test the chloride ion penetration resistance of concrete, which are the fast chloride ion migration coefficient method [ 34 , 35 ] and the electric flux method [ 36 ]. Electric flux is a parameter to evaluate the resistance of concrete to chloride ion penetration.…”
Section: Resultsmentioning
confidence: 99%